L’exploration des villes: les médiatisations visuelles entre mouvement et temporalité - D’Armenio, Enzo; Dondero, Maria Giulia (E|C, 2021)
Our intervention aims to address the modalities of exploration, data collection and analysis of urban space accomplished through different visual and interactive media. It consists of two parts. In the first part we want to investigate how artists and scientists have collected visual (and other) data that have been used as documents to study the city. We want to compare the strategies of data collection and the enunciative strategies of the resulting visualisations. In the second part, we propose a typology of virtual explorations of the city based on media practices implemented via various computer platforms. Virtual reality videos, on the other hand, allow for continuous exploration, organised by a prior staging, which leaves the angle of vision free in immersion. Finally, digital reproductions of cities - including those of video games and Digital Heritage projects - will complete our typology. Video games impose an active exploration of urban spaces, transforming it in accordance with a thematic scripting of movement.